Measurement of liquidity, insolvency and market risk levels in the textile sector of Ecuador - Orellana Osorio, Iván (2020)
A company is exposed to different types of financial risk (systematic and non-systematic risks). This research focuses on analyzing the insolvency, market and liquidity risks of the Textile Sector of Ecuador in the period 2007-2018. Regarding the methodology, a non-experimental study was carried out with a quantitative approach. The Superintendence of Companies, Securities and Insurance was used as a source of information; also scientific information on financial risk and the textile sector in Ecuador was analyzed. In the insolvency risk analysis, through the methodologies of Altman and Ohlson, it was determined that the riskiest years are 2016 and 2018: Altman score of 5,545 and 5,690 respectively, and a percentage of insolvency risk of 6,40% and 7,46% in the same years. In the market risk analysis, the Beta coefficient for the textile sector was 1,2. In addition, microenterprises have a higher level of liquidity risk, with 57,06%. Determining the financial risk of a company is an important tool for making decisions and helps to have a better vision of the fulfillment of the proposed objectives. URL: https://revistas.uta.edu.ec/erevista/index.php/bcoyu/article/view/1014